Efektivitas Pembelajaran Agama Islam terhadap Perkembangan Emosi dan Sosial Anak Akhir di Era Digitalisasi - Fitri Wijayanti; Avia Masliani; Yanto Abdilah; Ema Suraya; Muhammad Syifa Zakariya; Miftahul Huda (STIKes Ibnu Sina Ajibarang, 2026)
The rapid advancement of digital technology has significantly influenced various aspects of children's and adolescents' lives, particularly emotional development and social interaction. Excessive and uncontrolled use of digital media may negatively affect emotional regulation, communication skills, and interpersonal relationships. Therefore, educational institutions play an important role in helping students develop positive character and social behavior. Islamic Religious Education (IRE) is expected to contribute to character formation by instilling moral values, strengthening self-control, and encouraging healthy social interactions. This study aimed to analyze the effectiveness of Islamic Religious Education learning on the emotional development and social interaction of late childhood students in the digitalization era. A quantitative study with a cross-sectional design was conducted among 40 students at MIS As-Syafi'iyah 10 Bogor in 2026. Data were collected using structured questionnaires and analyzed using the Chi-square test. The findings revealed that 32 respondents (80%) demonstrated a good level of Islamic Religious Education learning. In addition, 23 respondents (57.5%) showed good emotional development, while 28 respondents (70%) demonstrated good social interaction. Statistical analysis showed a p-value of 0.001 (<0.05), indicating a significant effectiveness of Islamic Religious Education learning on students' emotional development and social interaction. These findings suggest that Islamic Religious Education contributes positively to fostering emotional maturity and improving social relationships among students in the digital era.